2018
DOI: 10.1155/2018/6703296
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Miswak (Salvadora persica) against Experimentally Induced Gastric Ulcers in Rats

Abstract: Gastric ulcers are among the most broadly perceived illnesses affecting individuals. Alcohol consumption is the main cause of gastric ulceration. This study assessed the protective effects of Salvadora persica (SP) extract against ethanol-induced gastric ulcer and elucidated the conceivable underlying mechanisms involved. For this purpose, 40 rats were allotted into 4 equal groups (control, ethanol- (EtOH-) treated, and SP-treated “SP200 and SP400” groups). The control and EtOH-treated groups were given phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…Our results are consistent with previous studies that have reported the ulcerative effect of orally applied ethanol on gastric mucosa [41–44, 4648]. It induces disruptions in gastric mucosal integrity, epithelial cellular exfoliation, mucosal friability, inflammation, and local hemorrhage due to intensive microvascular changes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous studies that have reported the ulcerative effect of orally applied ethanol on gastric mucosa [41–44, 4648]. It induces disruptions in gastric mucosal integrity, epithelial cellular exfoliation, mucosal friability, inflammation, and local hemorrhage due to intensive microvascular changes.…”
Section: Discussionsupporting
confidence: 93%
“…Some fixed vegetable oils extracted by various processes (solvent, supercritical CO 2 , and cold pressure) have been proven to heal skin wounds [4852]. In a previous work, we showed the effectiveness of Opuntia ficus indica oil (OFI oil) extracted by cold pressing on the healing of full-thickness skin injury, as well as its antimicrobial effect against bacteria, yeast, and fungi [53].…”
Section: Introductionmentioning
confidence: 99%
“…The first-strand cDNA was achieved using the HiSen Script cDNA (iNtRON Biotechnology, Inc.) package. Specific primers were used to amplify selected genes with glyceraldehyde 3-phosphate dehydrogenase (GAPDH) as a stable housekeeping gene ( Table S3 [ 57 , 58 , 59 , 60 , 61 , 62 ]). mRNA expression was achieved using a real-time Strata gene MX3005P PCR (Agilent Technologies, Santa Clara, CA, USA) and TOP real TM PreMIX SYBR Green qPCR master blend (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Nitric oxide is an important signal molecule and vasodilator agent, produced from L‐arginine by nitric oxide synthase (NOS) enzymes. Inducible NOS (iNOS)‐derived NO shows a positive effect on ulcer, whereas endothelial NOS (eNOS)‐derived NO has a negative effect via the formation of ROS on gastric ulcer (Lebda et al, ). NO has gastroprotective properties by regulating gastric pH and increasing blood flow (vasodilation effect).…”
Section: Discussionmentioning
confidence: 99%